2015
DOI: 10.1063/1.4935494
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt GaP/Si hetero-interface using bistepped Si buffer

Abstract: International audienceWe evidence the influence of the quality of the starting Si surface on the III-V/Si interface abruptness and on the formation of defects during the growth of III-V/Si heterogeneous crystal, using high resolution transmission electron microscopy and scanning transmission electron microscopy. GaP layers were grown by molecular beam epitaxy on vicinal Si (001). The strong effect of the Si substrate chemical preparation is first demonstrated by studying structural properties of both Si homoep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In early discussions on defect formation in planar epitaxial growth, and in more recent work, , it was shown that impurities located on the (hetero-) epitaxial interface can trigger bonding errors and SFs in {111} planes. The considered impurities can be extrinsic, e.g., carbon contamination, or intrinsic from a group III overdose, e.g., Ga cluster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early discussions on defect formation in planar epitaxial growth, and in more recent work, , it was shown that impurities located on the (hetero-) epitaxial interface can trigger bonding errors and SFs in {111} planes. The considered impurities can be extrinsic, e.g., carbon contamination, or intrinsic from a group III overdose, e.g., Ga cluster.…”
Section: Discussionmentioning
confidence: 99%
“…The considered impurities can be extrinsic, e.g., carbon contamination, or intrinsic from a group III overdose, e.g., Ga cluster. Therefore, rigorous surface cleaning and adjusted growth conditions were found to be critical to achieve defect-free epitaxy. , In ELO the crystal grows laterally over a SiO 2 stripe and thus follows a SiO 2 - III–V interface, which could also trigger SFs. For InP ELO on InP no SFs were observed in the overgrown layers, while in the heteroepitaxial case on a Si(001) substrate, rare occurrence of SFs was noticed and is suggested to stem from residual stress of the Si-InP heterojunction area.…”
Section: Discussionmentioning
confidence: 99%
“…Gallium phosphide is one of the most perspective candidates for fabrication of multi‐junction solar cells on silicon wafers. Firstly, lattice mismatch between Si and GaP is only 0.4% so GaP can be grown on silicon for the fabrication of the bottom subcell based on GaP/Si heterojunction by different epitaxial methods (MBE and VPE) . Further, novel materials (In)GaP(NAs) with small nitrogen content (called dilute nitrides) can be lattice‐matched to GaP.…”
Section: Introductionmentioning
confidence: 99%